Efektivitas Pemberian Rebusan Daun Kelor Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi di Desa Banyu Urip Gerung Lombok Barat - Yulinda Rahayu (Journal of Nursing Perspectives, 2025)
Hypertension is one of the non-communicable diseases that continues to be a major public health problem due to its high prevalence and the risk of causing serious complications such as stroke, heart disease, and kidney failure. Non-pharmacological efforts through the use of herbal ingredients such as Moringa oleifera (moringa leaves) are considered promising because of their bioactive compounds, including flavonoids, potassium, and sterols, which play roles as antihypertensive and antihyperlipidemic agents. This study aimed to determine the effectiveness of boiled moringa leaf decoction in reducing blood pressure among patients with hypertension in Banyu Urip Village, Gerung, West Lombok. The study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 18 respondents with hypertension selected using purposive sampling techniques. The intervention involved administering 150 ml of moringa leaf decoction every morning after breakfast for seven consecutive days. Blood pressure measurements were taken before and after the intervention using a sphygmomanometer. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. The results showed a significant decrease in respondents’ blood pressure. The mean systolic blood pressure before the intervention was 135.33 mmHg, which decreased to 122.50 mmHg after the intervention. The mean diastolic blood pressure before the intervention was 94.11 mmHg, which decreased to 84.56 mmHg afterward. Statistical analysis showed a p-value of 0.000 (< 0.05) for both systolic and diastolic pressures, indicating a significant effect of the moringa leaf decoction on reducing blood pressure. In conclusion, the moringa leaf decoction was effective in lowering both systolic and diastolic blood pressure among hypertensive patients. These findings support the use of herbal therapy as a complementary alternative for hypertension management in the community. It is recommended that healthcare services consider incorporating education on the use of moringa leaf decoction as a complementary therapy for hypertension control.